Judicial under-representation, over-representation and "catch up": insights from a study of US district court judges in the 10th Circuit. Issue 1 (2nd January 2019) - Wald, Eli
ABSTRACT: This essay examines the demographics of federal district court judges in the 10th Circuit. Consistent with the literature regarding the glass-ceiling effect in positions of power and influence in the legal profession, the study finds that women judges are under-represented on the 10th Circuit bench compared with their numbers as lawyers in the jurisdictions of the Circuit. However, the study finds that ethnic minority judges are over-represented in the Circuit. The essay next explores the relationship between under-representation, over-representation, discrimination and judicial "catch up": addressing historical and contemporary under-representation by means of temporary over-representation of qualified under-represented groups on the bench. It argues that under-representation that cannot be explained in terms of merit criteria or informed opting out strongly suggests the lingering effects of past discrimination, as well as the current effects of implicit bias. Such past explicit and present implicit discrimination ought to shift the burden of addressing under-representation to the institutional players involved in the judicial commission process, who should temporarily deploy over-representation to break through the glass-ceiling and catch up the disparity. The feasibility of such a judicial catch up is evidenced by the over-representation of ethnic minority judges in the 10th Circuit.